Morphological and multi-locus phylogenetic analyses reveal three new branched species of Clavaria (Clavariaceae, Agaricales) from China - Jun Yan; Li Xiong; Li-Xun Yang; Zheng-Mi He; Ping Zhang; Ke Liao (MycoKeys)
Based on morphological and molecular evidence, 12 specimens have been identified as belonging to three previously unrecognized species of Clavaria, which are here described as C. divergens, C. orientalis, and C. tongdaoensis. Clavaria divergens is characterized by its branched, white basidiomata. Clavaria orientalis and C. tongdaoensis are very similar to C. zollingeri in the field. However, C. orientalis is distinguished by its more robust branches, while C. tongdaoensis differs by its varied or paler color of basidiomata. A concatenated sequence dataset (ITS-nrLSU-RPB2) was used for multi-locus phylogenetic analysis. The phylogenetic tree of Clavaria showed that the three branched species each formed a distinct lineage with strong support. A key to the known branched species of Clavaria in China is provided.